Upaya peningkatan status kebersihan gigi dan mulut melalui siwak sebagai alat bantu sikat gigi - Asio, Asio; Sukarsih, Sukarsih; Silfia, Aida; Muliadi, Muliadi (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
The results of the seiwak research carried out by researchers in 2021 show that there is a significant difference in the mean OHI-S score between the use of siwak wood as a toothbrush tool in the intervention group and the control group who only brushed their teeth, namely -3,259 ± 0.00. This difference shows that using miswak as a toothbrush aid is more effective in cleaning teeth and mouth than just brushing your teeth. The results of an initial survey conducted at the Kumpeh Da Aru Attauhid Islamic boarding school, of the 10 students who were asked how and the benefits of miswak, only one person could answer. The type of service carried out to the village partner communities is a program to improve the level of dental and oral health at the Kumpeh Da Aru Attauhid Islamic Boarding School, Muaro Jambi Regency. Only 20.5% of respondents had a high level of knowledge before the intervention, namely 41 people consisting of 21.80% poor OHIS, 4% moderate, and 2% good. Respondents who had a high level of knowledge criteria after the intervention were 99%, namely 198 people consisting of 0% poor OHIS, 1% moderate, and 99% good. The statistical test output shows the p-value of knowledge and OHI-s of Santri is 0.000. Because the value of 0.0000 < 0.05 means there is a difference between the level of knowledge and OHI-IS pre-test and post-test, it can be concluded that community service by providing education on brushing teeth and using miswak as a tool can improve the OHI-S of students.